El juego de roles y su relación con la autoestima de las niñas y niños de primer grado de educación general básica de la escuela “Lauro Damerval Ayora N°1” de la ciudad de Loja, periodo lectivo 2013-2014. Lineamientos propositivos - León Villalta, Paulina Isabel (2014)
The present descriptive investigation of character, you denominated: THE GAME OF LISTS AND THEIR RELATIONSHIP WITH THE BASIC GENERAL EDUCATION FIRST GRADE CHILDREN SELF-ESTEEM "LAURO DAMERVAL AYORA N°1" SCHOOL OF THE LOJA CITY, PERIOD 2013-2014.PROPOTIONAL GUIDELINES. The present thesis had as general objective: To analyze the relationship of Game of Lists with the Self-esteem of thegame of lists and their relationship with the basic general education first grade children self-esteem "LauroDamervalAyora N°1"school of the loja city, period 2013-2014. Propotional guidelines The methods that were applied in the orientation and development of the investigation were: Scientific, Inductive, Deductive, Descriptive, Synthetic and The techniques and applied instruments were: the survey to the educational of the school "Laurel DamervalAyora N° 1, to determine the application of Games of Lists; and, the test of Self-esteem of Lewis R. Aiken, applied the children and girls, of the school "Laurel DamervalAyora N° 1" to value the Self-esteem. The Survey’s results applied to teachers, the 100% of educational interviewed in the daily planning uses the game of lists in the daily day of work, considering that the game is a didactic strategy that should be taken advantage of to the maximum thing in the process of the development of the self-esteem. According the results of self-esteem test of LEWIS R. AIKEN was determined that 40% of the children and girls of First Year of the School "Laurel DamervalAyora N°1" of the city of Loja they are located in the third step, obtaining a diagnosis of High Self-esteem, equivalent to Satisfactory; 29% is located in the fourth equivalent step to Very Satisfactory; 26% is located in the second equivalent step to Not very Satisfactory and 4% is located in the first step that is equal to Not Satisfactory, for what is demonstrated that, the great majority of children and girls have reached a good level of high self-esteem as a result of the work carried out by the educational ones based on the activities linked with the games of lists